ISLAMIC-BASED MEDIATION FOR STRENGTHENING FAMILY RESILIENCE: A COMMUNITY DEVELOPMENT APPROACH TO DAUGHTER-IN-LAW AND MOTHER-IN-LAW CONFLICT - Safithri, Awaliya; Khoir, Qoidul; Umam, M. Syafiqil; Riski, Mohammad; Ridho, Muhammad Ali Zainur (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the role of Islamic-based mediation in strengthening family resilience within Muslim communities, particularly in conflicts between daughters-in-law and mothers-in-law. Such conflicts represent a significant social issue that not only affects household harmony but also influences broader community stability. This research aims to analyze mediation practices and formulate a community-oriented mediation model grounded in Islamic family law principles. Using a qualitative multi-site case study approach, the research involved eight Muslim families experiencing in-law conflicts, as well as mediators including religious leaders and institutional actors. Data were collected through in-depth interviews, observations, and document analysis, and analyzed thematically. The findings reveal that conflicts are primarily triggered by parental interference, differences in values and parenting practices, and economic tensions. Effective mediation is characterized by the integration of Islamic values such as musyawarah (deliberation), ishlah (reconciliation), and justice; the balancing of power relations; and the establishment of clear agreements regarding roles and communication. These mediation practices contribute not only to conflict resolution but also to strengthening family resilience in psychological, social, and spiritual dimensions. This study proposes an Islamic relational mediation model that positions mediation as a community-based strategy for reinforcing social cohesion and family resilience. The findings highlight the importance of culturally grounded mediation in supporting sustainable community development within Muslim societies.